2022
DOI: 10.1186/s40645-022-00506-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of spatial and temporal variability of rainfall and their impact on rice production in Burma in 1901–1939 during the colonial period

Abstract: Climate is one of the main factors for rice crop growth. Understanding the relationship between climate variability and rice production during the period from 1901 to 1939 in Burma can give a clear picture of the impact of climate variability on rice yield since there were fewer human interventions on the catchment and almost no use of chemical fertilizer or high-yielding rice varieties at that time. However, the quantitative analysis of climate variability and its impact on rice production has not yet been pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The differences in the traits among different rice varieties are affected by the genetic characteristics of the rice varieties themselves, including growth duration ( Ping et al., 2018 ). The length of the growth duration is one of the key factors affecting crop growth, and previous studies have been conducted on this ( Wang et al., 2019 ; Ye et al., 2019 ; Shrestha et al., 2022 ). Research showed that if growth duration of rice was short, the vegetative growth duration was shortened, resulting in insufficient accumulation of nutrients in the early stage ( Ye et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in the traits among different rice varieties are affected by the genetic characteristics of the rice varieties themselves, including growth duration ( Ping et al., 2018 ). The length of the growth duration is one of the key factors affecting crop growth, and previous studies have been conducted on this ( Wang et al., 2019 ; Ye et al., 2019 ; Shrestha et al., 2022 ). Research showed that if growth duration of rice was short, the vegetative growth duration was shortened, resulting in insufficient accumulation of nutrients in the early stage ( Ye et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research showed that if growth duration of rice was short, the vegetative growth duration was shortened, resulting in insufficient accumulation of nutrients in the early stage ( Ye et al., 2019 ). However, if the growth duration of late rice was too long, the delay in heading stage will cause the daily average temperature and effective accumulated temperature in the filling stage to decrease, thus affecting the grain filling speed and time ( Shrestha et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%